PERLINDUNGAN HUKUM TERHADAP HARTA ANAK YANGDIKUASAI SECARA SEPIHAK OLEH ORANG TUA ANGKAT - Veby Annisa Fitri, - (2019)
Assets are often debated in a family business which also triggers and leads to a broken family relationship. legal protection of one's assets is important to protect the rights in the family to avoid greed. A family are two or more individuals who live in a household by blood relation, marriage, or adoption. They interact with each other, have respective roles, right, and obligation, and create and maintainculture. Adoption is a legal action to adopt someone's child to be their own child. Each family will always face various problems, either from the outside and from within. In order to overcome those problems, solutions must be initiated by the family or by an expert who can help to overcome family problems if it requires others to help to resolve the conflicts. The problem can be prevented by improving relationships in the family and also with the help from others as an effort to help the family resolve the problem. As a law state, Indonesia guarantees all of the rights of its citizens in position in the law and must uphold the law. On this basis the author takes the issue of how to protect the law of the assets of children who are unilaterally controlled by foster parents and whether foster parents deserve a part of the assets of adopted children.